PETA KEMAMPUAN KEUANGAN DAERAH DAN KONSEKUENSINYA TERHADAP BELANJA DAERAH PADA ERA OTONOMI DAERAH ( Studi Kasus diKabupaten/Kota Provinsi Jawa Tengah ) - Mochamad Mahlul Arizal, 11.4202.0015 (Students Journal of Accounting and Banking, 2013)
Along with the development of desentralization, the general financial condition of each region should be supported by the funding that comes from local revenue (PAD). These areas have had the authority to regulate and manage the resources contained in the region itself, meaning that the area required to manage the development of the region independently. This is a consequence of the fulfillment of fiscal independence and freedom in collecting local revenues. This research is intended to determine the map of financial performance  during the era of decentralization. Also find out the extent to which the degree and development of fiscal autonomy at the regency / city in Central Java and know the influent of Common Allocation Fund (DAU) and Local Revenue (PAD) on regional expenditure. The map of financial performance is determined by two indicators,  they are regional growth of local revenue (PAD) and share of local revenue towards total regional expenditure. Multiple regression was used as analysis tool. There are two variables in this research, independent variable and dependent variableCommon Allocation Fund (DAU) and Local Revenue ( PAD) as the independent variables and Regional Expenditure as a dependent variable. The secondary data is used in this research in the form of time series data which is found at the realization report of APBD on regency/city in Central Java Province from 2001 to 2011. The results of this research shows that (1) on Financial Performance Map of regency/City Central Java Province is known that most (97%) regions have low financial capability which the growth of revenue in this areas quite high, but the it has not yet been able to increase the independence of the region. (2) From DOF analysis shows that 68.6%  of regencies / cities in Central Java include on very low criteria which DOF average is between 0-10%. (3) local expenditure in Central Java province was more influenced by DAU than PAD.  It means that there is flypaper effect. Key Words : Degree of Fiscal Autonomy, Growth PAD, Share PAD, DAU, Expenditure Financial Capability Level